PENERAPAN PENDEKATAN KONTEKSTUAL DALAM MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENCAPAI HASIL BELAJAR MATERI PERPINDAHAN KALOR PADA SISWA KELAS VII SMP NEGERI 2 AMBON - Nur Hamida Siregar (Jurnal Muara Pendidikan, 2019)
The quality of education in Indonesia was in the worst position in Asian from 12 countries surveyed in 2010 by PERC, so more efforts by teachers are needed to improve the quality of education. One of the efforts is through the application of good and appropriate learning models to the characteristics of subjects. This study aimed to determine the achievement of learning outcomes of heat transfer subject of students of class VII6 SMP Negeri 2 Ambon through application of a contextual approach in Jigsaw type cooperative learning model. This research was a quantitative descriptive, with 40 students. This study found that the average score of initial achievement was 29.22 (failed qualification). While during the learning process with Jigsaw cooperative learning model, the average cognitive achievement was 83.34 (good qualification), affective was 82.66 (good qualification), and psychomotor was 88.75 (good qualification). While there were formative test results obtained the average achievement score was 74.77 (sufficient qualification), and the average of the final score was 81.71 (good qualification). It can be concluded that the learning process by applying a contextual approach in Jigsaw type cooperative learning model was proven to help students in achieving the learning outcomes of heat transfer subject.